Evaluation of Immunogenicity and Protective Efficacy Elicited by Mycobacterium bovis BCG Overexpressing Ag85A Protein against Mycobacterium tuberculosis Aerosol Infection - Xu, Zheng Zhong; Chen, Xiang; Hu, Ting; Meng, Chuang; Wang, Xiao Bo; Rao, Yan; Zhang, Xiao Ming; Yin, Yue Lan; Pan, Zhi Ming; Jiao, Xin An (Frontiers in Cellular and Infection Microbiology, 2016)
Mycobacterium bovis bacillus Calmette-Guérin (BCG) is currently the only vaccine available against tuberculosis (TB), however, it has various levels of efficacy for preventing pulmonary TB. In this study, a recombinant BCG (rBCG::Ag85A) strain overexpressing the immunodominant Ag85A antigen was constructed, and its immunogenicity and protective efficacy were evaluated. The results showed that the Ag85A protein was successfully overexpressed in rBCG::Ag85A, the Ag85A peptide–MHC complexes on draining lymph node dendritic cells of C57BL/6 mice infected with rBCG were detectable 4 h post-infection. The C57BL/6 mice infected with this strain had stronger antigen-specific interferon-gamma (IFN-γ) responses and higher antibody titers than those immunized with BCG, and the protective experiments showed that the rBCG::Ag85A can provide higher but not significantly protective efficacy against Mycobacterium tuberculosis (M. tuberculosis) H37Rv infection compared with BCG vaccine. Therefore, our results demonstrated the potential of rBCG::Ag85A as a vaccine candidate against TB.